A novel carotenoids-producing marine bacterium from noble scallop Chlamys nobilis and antioxidant activities of its carotenoid compositions. (1st August 2020) - Liu, Hongxing; Zhang, Chuanxu; Zhang, Xinxu; Tan, Karsoon; Zhang, Hongkuan; Cheng, Dewei; Ye, Ting; Li, Shengkang; Ma, Hongyu; Zheng, Huaiping
Highlights: A novel carotenoid-producing bacterium was isolated from gut of a noble scallop. The high carotenoids content was produced by the Brevundimonas scallop . 2, 2′-Dihydroxy-astaxanthin has stronger antioxidative activity than astaxanthin. Genomic-metabolomic approach can better characterize bacterial metabolites. Abstract: Marine bacteria produce many bioactive compounds, including carotenoids. However, the quality of bacterium carotenoids is relatively unknown. Therefore, in this study, a novel carotenoids-producing bacterium Brevundimonas scallop Zheng & Liu was isolated from Chlamys nobilis . The genome of the isolate was analyzed, carotenoid compounds were screened using HPLC-MS and the carotenoid production in B. scallop was monitored. The results revealed that the genome of B. scallop contained a carotenoid synthesis gene cluster, which involved in astaxanthin and hydroxy-astaxanthin biosynthesis. The 2, 2′-dihydroxy-astaxanthin was the major carotenoid produced by B. scallop . The optimum culture condition for the highest carotenoids production (1303.62 ± 61.06 µg/g dry cells) for B. scallop was at temperature and salinity of 20 °C and 3% salt, respectively, in 10 g/L glucose as carbon source. The results showed the B. scallop is a new carotenoids resource in marine bivalve, which has an excellent antioxidative activity and potential industrial use.